Molecular Networking Analysis and Antibacterial Potential of Ethyl Acetate Extracts of Sinomicrobium sp. PAP.21 using OSMAC Method - Harwoko, Harwoko; Rahmawati, Anggun Tri; Riyanti, Riyanti (Majalah Obat Tradisional, 2024)
Challenges in drug discovery include biosynthetic gene clusters which remain silent under standard laboratory culture conditions. On the other hand, the rediscovery of the known compounds is inevitable. Accordingly, One Strain-MAny Compounds (OSMAC) approach and molecular networking analysis are currently applicable to discovering new bioactive compounds. Sinomicrobium sp. PAP.21 isolated from marine sediment collected in Cenderawasih Bay, West Papua, was added to the culture. Then, the bacterium was cultured in five different liquid media (RL1, A1BFe+C, NB, LB, and seawater) and incubated for 4, 5, and 7 days. The bacterial cultures were extracted using ethyl acetate (EtOAc) separately for each medium and incubation period, followed by LC-HRMS measurement. A total of 45 ethyl acetate extracts were assayed for in vitro antibacterial activity against Micrococcus luteus and Escherichia coli. Molecular networking analysis through GNPS indicated that three putative compounds possess antibacterial properties. EtOAc extracts from the A1BFe+C medium demonstrated antibacterial activity against M. luteus. However, none of them were active against E. coli. Collectively, Sinomicrobium sp. PAP.21 produced bioactive compounds exhibiting antibacterial potential, particularly against Gram-positive bacteria.